THE EFFECTIVENESS OF ENVIRONMENTAL LEARNING MODEL ON STUDENTS' MOTIVATION AND LEARNING OUTCOMES - Warda Murti; Sri Maya (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:This study aims to determine the effectiveness of the environmental learning model on the students' motivation and learning outcomes in Biology Education Study Program at Muslim University of Maros. This research is a quantitative study using a pre-experimental design with One-Shot Case. The class was taught online using Google Classroom application. The subjects in this study were the fourth-semester students of Biology Education Study Program consisting of 16 students in the Natural Resource Management course. The instruments used in this study were questionnaires and tests. The data was then analyzed using descriptive and inferential statistics. The findings indicated that the environmental learning model effectively increased students' motivation and learning outcomes with average scores of 84.73% and 77.33%, respectively.Abstrak:Penelitian ini bertujuan untuk mengetahui keefektifan model pembelajaran environmental learning terhadap motivasi dan hasil belajar mahasiswa Program Studi Pendidikan Biologi Universitas Muslim Maros. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan pre-eksperimen dengan desain One Shot Case. Kelas diajarkan secara online menggunakan aplikasi Google Classroom. Subjek dalam penelitian ini adalah mahasiswa semester IV Program Studi Pendidikan Biologi yang terdiri dari 16 mahasiswa pada mata kuliah Pengelolaan Sumber Daya Alam. Instrumen yang digunakan dalam penelitian ini adalah angket dan tes. Data tersebut kemudian dianalisis menggunakan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa model pembelajaran lingkungan efektif dalam meningkatkan motivasi dan hasil belajar siswa dengan nilai rata-rata masing-masing 84,73% dan 77,33%.